Na encruzilhada do capitalismo dependente: migrações forçadas e o fluxo de venezuelanos no brasil - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
The Venezuelan issue is a factor close to the Brazilian reality, both from geographic aspects, given the territorial proximity between Brazil and Venezuela, and from historical and economic aspects, in which both countries are important components of global capitalism. With the recent Venezuelan crisis, a large contingent of immigrants crossed Brazil’s borders from 2018 onwards, a scenario in which the proximity between neighboring countries became more evident. In this sense, the present work starts from the analysis of the economic situation in Latin America, inserted in a global economic panorama, from the perspective of the Marxist Theory of Dependency, seeking to understand the impact of dependent capitalism on Venezuelan immigrants in Brazil. To this end, we seek, through bibliographical review and analysis of data and documents, published in official bodies, to understand the reality of the immigrant worker in the context of Latin American dependent capitalism.
At the crossroads of dependent capitalism: forced migrations and the flow of Venezuelans in Brazil
Keywords: Crise venezuelana; Capitalismo Dependente; Teoria Marxista da Dependência; Venezuelan crisis; Dependent Capitalism; Marxist Dependency Theory; CIENCIAS SOCIAIS APLICADAS::ECONOMIA